Aplikasi Uji Kuat Geser Dalam Remediasi Lereng Tambang Aspal Di PT Karunia Alam Indonesia Kec. Lasalimu Kab. Buton, Provinsi Sulawesi Tenggara - Novandri Kusuma Wardana (PROMINE, 2017)
Mining activities iscommonlyto work with the problem of deformation or rock movement, this is causingthe shift of rock mass and generated in the occurrence of landslides activity. Slope Stability Analysisrequired that the slope in stable condition. Therefore, stable bench is needed to prevent failure benchthat bring about interference either tool traffic or loading material during production process. Testing ofUCS value is done on 6 lithology that is on asphalt lithology, mudstone, siltstone, sandstone andclaystone. Based on the results of laboratory testing show that value of cohesion and friction angle togenerate by using Generalized Hoek Brown Failure Criterion method.The values of cohesion andfriction angle in asphalt are 0.080712 MPa and 26.3176 º. Asphalt Rock Mass Strength Value is0.145453 MPa. The values of cohesion and friction angle in mudstone are 0.075424 MPa and17.4773º. Rock Mass Value The mudstone rock is 0.220617 MPa. The values of cohesion and frictionangle in siltstone are 0,105107 MPa and 28,2864º. Rock Mass Strength siltstone rock is 0.311426MPa. The values of cohesion and friction angle in the sandstone are 0.180389 MPa And 38.9621º.Rock mass strength sandstone rock is 0.739092 MPa. The values of cohesion and friction angle insiltstone are 0.180389 MPa And 38.9621º. The Power of Mass The siltstone rock is 0.739092MPa.The values of cohesion and friction angle in mudstone are 0.180389 MPa And 38.9621º. RockMass Strength value The mudstone rock is 0.739092 MPa. Given that in Geological Strength Indexmethod only qualitative data will be more accurate using RMR method so it can get quantitative data.